O canto da família: organização vocal nas Folias de Reis do Sudeste brasileiro - Reily, Suzel Ana (Revista do Instituto de Estudos Brasileiros, 1988)
This is an ethnomusicological analysis of the Folia de Reis in the Southeastern region of Brazil. The Folias are made up of a group of musicians that roam from house to house during the Christmas season, as a form of devotion to the three Wise Men. In an attempt to understanding the logic behind the distribution of the voices whithin the song style, I concentrated the analysis on the style the musicians call "old tune", for it is the most complex form found in the region of the research project. Since I noted that the vocal organization reflects normative notions regarding family structure among the communities that participate in the tradition, we can view the music as a social construction, in which the group says something fundamental about its own worldview.